The Effect of Roof Slope and Orientation on the Performance of On-Grid PV Plants in Central Java, Indonesia - Umam, Mukhamad Faeshol; Patria, Mochamad Febrian Adhi; Fitri, Sanira; Cantika, Mauria; Pramudya, Wulan Regina; Farras, Hani Aulia (UIR PRESS, 2026)
This study presents a comprehensive five-year performance analysis of four 20 kWp grid-connected rooftop photovoltaic plants in Central Java, Indonesia, to evaluate the impact of roof slope and orientation. The research identifies an optimal configuration of 20° tilt with a Northeast (45°) orientation, which yielded a peak DC power of 15.2 kW and demonstrated the highest initial and long-term energy production. However, this investigation reveals that one system with a near-optimal geometry suffered a failure, reducing its output by over 70% due to a single-array fault, while a suboptimal dual-orientation system maintained higher production through consistent operation. The data conclusively shows that performance degradation and component failure can outweigh the advantages of an optimal roof design. The study concludes that the economic viability of rooftop PV in Central Java is contingent upon a dual strategy: prioritizing optimal roof geometry for maximum energy potential, and implementing a proactive operations and maintenance regime to protect the investment. These findings provide an evidence-based guidance for stakeholders to optimize both the design and lifetime performance of solar energy systems.